Influence of principal leadership and education financing management against school productivity in public high school (SMAN) - Asep Kurniawan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The main problem revealed in this study is how the influence of principal leadership and education financing management affects school productivity both partially and collectively. The research method used was the explanatory survey method, with a five-category Likert scale questionnaire data collection technique, on 124 state high school teachers in Bandung City. The data processing technique used is path analysis modeling. This technique is used to determine the direct and indirect influence of exogenous variables on endogenous variables. The significance test uses the F-test and the t-test. The results showed that school productivity in state high schools tends to be high, as indicated by the indicators that form school productivity, which tend to be high as well. The high level of school productivity is influenced by the leadership of high-level principals who are able to manage education financing properly. This study recommends to schools that they improve the factors that are still considered low, as shown by the average score of the indicators that can be seen in the discussion of this study at Bandung.